Proposal for use of Dematel model in combination with FMEA and FMECA methods - Gula, Adrian; Bujna, Marián; Lee, Chia Kuang; Drlička, Róbert (Sciendo, 2025)
The elimination of time, cost, and material losses is the ultimate goal of any organization. Reliability can also negatively impact these losses; therefore, our aim is to use tools which can prevent this from occurring. In this paper, a combination of the FMEA, FMECA, and DEMATEL methods was used to identify the critical points of the system to propose corrective actions more effectively. The study identified two failure modes FM1 and FM2 with five effects (Ei) and causes (Ci). It was found that FM2 achieved a higher RPN value in FMEA, meanwhile FM1 was evaluated as a failure mode with higher criticality (CA). Since the basis of RPN and CA calculations are variables S (severity of effects) and O (occurrence of causes), DEMATEL was used to evaluate the relations between Ei and Ci. A new model was created to better visualise the relations between each Ei and Ci. Then, these factors were classified into quadrants according to the DEMATEL model cause-and-effect digraph and based on direct influence matrix, the quantification of these factors was proposed. This innovative visualisation solution allowed us to identify FM1 (with E1 and E3 effects as well as C1 and C3 causes) as a priority for corrective action.